Penguatan Literasi Sains: Pelatihan Pembuatan Buku Cerita Digital Berbasis Kearifan Lokal Kalimantan Selatan - Isna Kasmilawati; Nana Citrawati Lestari; Lili Agustina (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
Good literacy skills can develop critical, creative, and noble thinking patterns. Therefore, teachers play a crucial role in improving students' literacy skills at school. The challenge faced by the partner school, SD Muhammadiyah Al Mukhlishin, is the difficulty in designing digital learning resources that incorporate local values relevant to the students' surroundings. Therefore, teacher training in designing digital learning resources, specifically storybooks based on local wisdom, is essential to implement. The objectives of this Community Service Program are to enhance teachers' understanding of literacy and science concepts and to improve their skills in creating and designing storybooks based on the local wisdom of South Kalimantan using Canva, Meta AI, ChatGPT, and Hayzine. This PKM activity took the form of a training program attended by 25 participants, with the output being a collection of children's storybooks in digital format. Based on pre-test and post-test scores, there was an improvement in participants' scores. The lowest pre-test score was 60, and the highest was 90, with an average pre-test score of 69.2. The post-test results showed the lowest score of 80 and the highest of 100, with an average post-test score of 94. Participants experienced an increase in scores of 24.8 points, or 35.8%. Based on the questionnaire distributed with aspects assessed on 10 indicators, it can be concluded that the percentage criteria of the training participants' answers were categorized as Very Good.